Effect of screening, brief intervention and referral to treatment for unhealthy alcohol and other drug use in mental health treatment settings: a randomized controlled trial. (5th July 2020) - Karno, Mitchell P.; Rawson, Richard; Rogers, Benjamin; Spear, Suzanne; Grella, Christine; Mooney, Larissa J.; Saitz, Richard; Kagan, Bruce; Glasner, Suzette
Abstract: Aims: To test the efficacy of a brief intervention to reduce alcohol or drug use and to promote use of addiction services among patients seeking mental health treatment. Design and setting: A multi‐centre, longitudinal, two‐group randomized controlled trial with randomization within each of two mental health treatment systems located in Ventura County and Los Angeles County in California, USA. Participants: A total of 718 patients (49.2% female) aged 18 and older with a mental health diagnosis and either a heavy drinking day or any use of cannabis or stimulants in the past 90 days. Intervention and comparator: A motivation‐based brief intervention with personalized feedback (screening, brief intervention and referral to treatment (SBIRT) condition) ( n  = 354) or a health education session (control condition) ( n  = 364). Measurements: Primary outcomes included frequency of heavy drinking days, days of cannabis use and days of stimulant use at the primary end‐point 3 months post‐baseline. Secondary outcomes included frequency and abstinence from substance use out to a 12‐month follow‐up and the use of addiction treatment services. Findings: Participants in the SBIRT condition had fewer heavy drinking days [odds ratio (OR) = 0.53; 95% credible interval (CrI) = 0.48–0.6] and fewer days of stimulant use (OR = 0.58; 95% CrI = 0.50–0.66) at the 3‐month follow‐up compared with participants in the health education condition. Participants in the SBIRT condition did not comparatively reduce days of cannabis use at the 3‐month follow‐up (OR = 0.93; 95% CrI = 0.85–1.01). Secondary outcomes indicated sustained effects of SBIRT on reducing the frequency of heavy drinking days and days of stimulant use. No effects were observed on abstinence rates or use of addiction treatment services. Conclusions: Screening and brief intervention for unhealthy alcohol and drug use in mental health treatment settings were effective at reducing the frequency of heavy drinking and stimulant use.